The Effect of Organizational Climate on the Psychological Resilience of Employees in Hotel Organizations: An Applied Study in First-Class Hotels in Baghdad (Al-Mostansiriyah journal for Arab and international studies, 2026)
AbstractThe aim of this research is to identify the relationship and impact of the organizational climate, with its various dimensions, on employees’ psychological resilience, also examined through its multiple dimensions, within hotel business organizations.The significance of the study stems from the importance of the selected variables. The independent variable, organizational climate, includes: communication, managerial authority, decision-making, motivation, and organizational structure. The dependent variable, psychological resilience, includes: positive thinking, self-confidence, adaptability, and analytical ability.The study was conducted in six top-tier hotels in Baghdad, where the opinions of a sample of hotel managers and department heads were surveyed. The sample included 24 individuals. To investigate the relationship and influence between the organizational climate and psychological resilience, the study employed a questionnaire comprising 36 comprehensive items related to the research variables.The study yielded several conclusions, the most important of which is the existence of a strong correlation between organizational climate and employees’ psychological resilience. Additionally, it concluded that the organizational climate and its dimensions have a significant and effective impact on employees' psychological resilience.The research concluded with a number of recommendations, most notably the need to raise awareness among managers and employees in the tourism sector regarding the importance of supporting psychological resilience. It is a fundamental component in building adaptive systems for all employees to help them face psychological pressures within hotel organizations. This, in turn, would help establish a stable workforce in these organizations and enhance their role as a vital pillar of tourism services in Iraq.Keywords: Organizational climate, psychological resilience of employees in hotel business organizations.